Caste comparisons: Evidence from India - Xavier Fontaine; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2013)
The caste issue dominates a large part of India's social and political life. Caste shapes Indians' identities, and strong tensions exist between castes. This paper evaluates how caste-based comparisons may be exacerbated in such a conflictual context. Using subjective well-being data from an original panel survey, together with a national representative survey on expenditure, we find that both within-caste comparisons and between-rival-caste comparisons reduce well-being. Between-caste comparisons affect well-being three times more than within-caste comparisons. In absolute value, an increase in rival castes' expenditure affects well-being as much as own expenditure. These findings highlight the strength of comparisons between rival castes. Yet this comparison scheme turns out to be asymmetrical: only low castes care about the economic successes of their rivals, and only high-caste Indians compete with their fellows.
Keywords: 330; Subjective Well-being; Relative Utility; Caste classes; India; Panel Data; Zufriedenheit; Soziale Schicht; Indien